The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Leading Indicators for Farmers’ Work Health and Safety in Western Agricultural Systems: A Systematic Review - Carlos Mesa Castrillon; Kerri-Lynn Peachey; Lisa Harrison; Richard Franklin; David Lyle; Tony Lower (Journal of Agromedicine, 2026)

Assessment of injector-flow characteristics of additised and renewable diesel blends through high-speed imaging - Onur Baran; Ioannis K. Karathanassis; Phoevos Koukouvinis; Joonsik Hwang; Lyle M. Pickett; David Spivey; Manolis Gavaises (Fuel, 2023)

Toward sustainable harvest strategies for marine fisheries that include recreational fishing - Ashley M. Fowler; Natalie A. Dowling; Jeremy M. Lyle; Josep Alós; Leif E. Anderson; Steven J. Cooke; Andy J. Danylchuk; Keno Ferter; Heath Folpp; Clifford Hutt; Kieran Hyder; Daniel K. Lew; et al. (Fish and Fisheries, 2023)
Recreational fishing (RF) is a large yet undervalued component of fisheries globally. While progress has been made in monitoring, assessing, and managing the sector in isolation, integration of RF into the management of multi‐sector fisheries has been limited, particularly relative to the commercial sector. This marginalises recreational fishers and reduces the likelihood of achieving the sector's objectives and, more broadly, achieving fisheries sustainability. We examined the nature and extent of RF inclusion in harvest strategies (HSs) for marine fisheries across 15 regions in 11 nations to define the gap in inclusion that has developed between sectors. We focused on high‐income nations with a high level of RF governance and used a questionnaire to elicit expert knowledge on HSs due to the paucity of published documents. In total, 339 HSs were considered. We found that RF inclusion in HSs was more similar to the small‐scale sector (i.e., artisanal, cultural, or subsistence) than the commercial sector, with explicit operational objectives, data collection, performance indicators, reference points, and management controls lacking in many regions. Where specified, RF objectives focused on sustainability, economic value and catch allocation rather than directly relating to the recreational fishing experience. Conflicts with other sectors included competition with the commercial sector for limited resources, highlighting the importance of equitable resource allocation policies alongside HSs. We propose that RF be explicitly incorporated into HSs to ensure fisheries are ecologically, economically, and socially sustainable, and we recommend that fisheries organisations urgently review HSs for marine fisheries with a recreational component to close the harvest strategy gap among sectors.

Effects of marine diesel on microbial diversity and activity in high Arctic beach sediments - Margaux Durand; David Touchette; Ya-Jou Chen; Elisse Magnuson; Jessica Wasserscheid; Charles W. Greer; Lyle G. Whyte; Ianina Altshuler (Marine Pollution Bulletin, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Short-stature and tall maize hybrids have a similar yield response to split-rate vs. pre-plant N applications, but differ in biomass and nitrogen partitioning - Kevin R. Kosola; Magen S. Eller; Frank G. Dohleman; Lia Olmedo-Pico; Brad Bernhard; Eric Winans; Ty J. Barten; Lillian Brzostowski; Lesley R. Murphy; Chiyu Gu; Lyle Ralston; Mike Hall; et al. (Field Crops Research, 2023)

Particulate Matter Emissions in Gasoline Direct-Injection Spark-Ignition Engines: Sources, Fuel Dependency, and Quantities - Eshan Singh; Namho Kim; David Vuilleumier; Scott Skeen; Emre Cenker; Magnus Sjöberg; Lyle Pickett (Fuel, 2023)

Evaluation of a water arsenic filter in a participatory intervention to reduce arsenic exposure in American Indian communities: The Strong Heart Water Study - Tracy Zacher; Kelly Endres; Francine Richards; Lisa Bear Robe; Martha Powers; Joseph Yracheta; David Harvey; Lyle G. Best; Reno Red Cloud; Annabelle Black Bear; Steve Ristau; Dean Aurand; et al. (Science of The Total Environment, 2023)

Biodegradation potential of residue generated during the in-situ burning of oil in the marine environment - Ruby Pyke; Nathalie Fortin; Jessica Wasserscheid; Julien Tremblay; Lars Schreiber; Marie-Josee Levesque; Stephanie Messina-Pacheco; Lyle Whyte; Feiyue Wang; Kenneth Lee; David Cooper; Charles W. Greer (Journal of Hazardous Materials, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Recreational sea fishing in Europe in a global context—Participation rates, fishing effort, expenditure, and implications for monitoring and assessment - Kieran Hyder; Marc Simon Weltersbach; Mike Armstrong; Keno Ferter; Bryony Townhill; Anssi Ahvonen; Robert Arlinghaus; Andrei Baikov; Manuel Bellanger; Janis Birzaks; Trude Borch; Giulia Cambie; et al. (Fish and Fisheries, 2018)
Marine recreational fishing ( MRF ) is a high‐participation activity with large economic value and social benefits globally, and it impacts on some fish stocks. Although reporting MRF catches is a European Union legislative requirement, estimates are only available for some countries. Here, data on numbers of fishers, participation rates, days fished, expenditures, and catches of two widely targeted species were synthesized to provide European estimates of MRF and placed in the global context. Uncertainty assessment was not possible due to incomplete knowledge of error distributions; instead, a semi‐quantitative bias assessment was made. There were an estimated 8.7 million European recreational sea fishers corresponding to a participation rate of 1.6%. An estimated 77.6 million days were fished, and expenditure was €5.9 billion annually. There were higher participation, numbers of fishers, days fished and expenditure in the Atlantic than the Mediterranean, but the Mediterranean estimates were generally less robust. Comparisons with other regions showed that European MRF participation rates and expenditure were in the mid‐range, with higher participation in Oceania and the United States, higher expenditure in the United States, and lower participation and expenditure in South America and Africa. For both northern European sea bass ( Dicentrarchus labrax , Moronidae) and western Baltic cod ( Gadus morhua , Gadidae) stocks, MRF represented 27% of the total removals. This study highlights the importance of MRF and the need for bespoke, regular and statistically sound data collection to underpin European fisheries management. Solutions are proposed for future MRF data collection in Europe and other regions to support sustainable fisheries management.

Regional engagement and spatial modelling for natural resource management planning - Wayne S. Meyer; Brett A. Bryan; David M. Summers; Greg Lyle; Sam Wells; Josie McLean; Mark Siebentritt (Sustainability Science, 2016)

The border-to-border distribution method for analysis of cytoplasmic particles and organelles - Shalane K. Yacovone; David A. Ornelles; Douglas S. Lyles (Cell and Tissue Research, 2016)

Revisiting the past to foretell the future: summer temperature and habitat area predict pika extirpations in California - Joseph A. E. Stewart; John D. Perrine; Lyle B. Nichols; James H. Thorne; Constance I. Millar; Kenneth E. Goehring; Cody P. Massing; David H. Wright (Journal of Biogeography, 2015)
Aim The American pika ( Ochotona princeps ) appears to have experienced climate‐mediated upslope range contraction in the Great Basin of North America, but this result has not yet been extended to other portions of the pika's range. Our goals were: first, to determine the environmental parameters that most influence current pika distribution within California; second, to infer whether these constraints explain extirpations that have occurred in California; third, to predict future extirpations; and fourth, to advance methods for assessing the degree to which pikas and other climate‐sensitive mammals are threatened by climate change. Location Historical pika record locations in California, USA , spanning four degrees of latitude and longitude, from Mount Shasta to the southern Sierra Nevada. Methods We identified 67 precise historical pika record locations and surveyed them exhaustively, over multiple years, to determine whether pika populations persist at those sites. We used an information theoretic approach and logistic regression to model current pika occupancy as a function of 16 environmental variables, tested our best‐performing model as a predictor of historical occupancy, and then used our model to predict future pika occupancy given anticipated climate change. Results Pikas no longer occurred at 10 of 67 (15%) historical sites in California. The best predictors of occupancy were average summer temperature and talus habitat area within a 1‐km radius. A logistic model fitted to this relationship correctly predicted current occupancy at 94% of sites and correctly hindcasted past occupancy at 93% of sites, suggesting that the model has strong temporal transferability. Depending on the future climate scenario, our model projects that by 2070 pikas will be extirpated from 39% to 88% of these historical sites in California. Main conclusions Our simple species distribution model for pikas performs remarkably well for both current and historical periods. Pika distribution appears to be governed primarily by behavioural restrictions mediated by summer temperature and by the configuration of talus habitat available to pikas locally. Pikas, and other montane species in the western USA, may be subjected to above‐average exposure to climate change because summer temperature is projected to rise more than annual temperature.

Simian immunodeficiency virus-specific CD4+ T cells from successful vaccinees target the SIV Gag capsid - Juan P. Giraldo-Vela; Alex T. Bean; Richard Rudersdorf; Lyle T. Wallace; John T. Loffredo; Priscilla Erickson; Nancy A. Wilson; David I. Watkins (Immunogenetics, 2010)

Analyses of associations with asthma in four asthma population samples from Canada and Australia - Denise Daley; Mathieu Lemire; Loubna Akhabir; Moira Chan-Yeung; Jian Qing He; Treena McDonald; Andrew Sandford; Dorota Stefanowicz; Ben Tripp; David Zamar; Yohan Bosse; Vincent Ferretti; et al. (Human Genetics, 2009)

A hypothesis regarding vascular acoustic emission accompanying arterial injury induced by balloon angioplasty - Michael J. Vonesh; Lyle F. Mockros; Charles J. Davidson; Krishnan B. Chandran; David D. McPherson (Annals of Biomedical Engineering, 1997)